2022
DOI: 10.48550/arxiv.2206.14225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Normalized Autoencoder for LHC Triggers

Abstract: Autoencoders are the ideal analysis tool for the LHC, as they represent its main goal of finding physics beyond the Standard Model. The key challenge is that out-of-distribution anomaly searches based on the compressibility of features do not apply to the LHC, while existing density-based searches lack performance. We present the first autoencoder which identifies anomalous jets symmetrically in the directions of higher and lower complexity. The normalized autoencoder combines a standard bottleneck architectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…While this is not strictly density estimation, the optimisation is highly aligned with learning a density, since regions of the phase space which are most populated are those which should be reconstructed the best and thus have the lowest anomaly score. There has been significant progress with the AutoEncoder tools and other density-based anomaly detection methods in recent years [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], with studies covering interpretability of AutoEncoders [34,35], topic modelling [36,37], null hypothesis tests for anomaly detection [38], ABCD methods [39], the Normalised AutoEncoder (NAE) [40], and normalising flow techniques [41][42][43][44]. For a comprehensive summary of many different anomaly detection methods we refer the reader to the community challenge papers in Refs [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…While this is not strictly density estimation, the optimisation is highly aligned with learning a density, since regions of the phase space which are most populated are those which should be reconstructed the best and thus have the lowest anomaly score. There has been significant progress with the AutoEncoder tools and other density-based anomaly detection methods in recent years [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], with studies covering interpretability of AutoEncoders [34,35], topic modelling [36,37], null hypothesis tests for anomaly detection [38], ABCD methods [39], the Normalised AutoEncoder (NAE) [40], and normalising flow techniques [41][42][43][44]. For a comprehensive summary of many different anomaly detection methods we refer the reader to the community challenge papers in Refs [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…However, they are of a different nature than most current implementations of generative networks which are based on variations of Autoencoders (see e.g. [42][43][44][45][46]), Generative Adversarial Networks (see e.g. [44,47]), Normalizing Flows (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, the rapid development of machine learning to the analysis of jet energy depositions [19,22,27] demonstrated that jet tagging strategies, including those for semivisible jets, can be learned directly from lower-level jet constituents without the need to form physics-motivated high level observables [17,28]. Such learned models are naturally challenging to interpret, validate or quantify uncertainties, especially given the highdimensional nature of their inputs.…”
Section: Jhep12(2022)132 1 Introductionmentioning
confidence: 99%